Prenatal prediction of pulmonary arterial hypertension in congenital diaphragmatic hernia. (May 2015) - Spaggiari, E.; Stirnemann, J. J.; Sonigo, P.; Khen‐Dunlop, N.; De Saint Blanquat, L.; Ville, Y.
ABSTRACT: Objective: To evaluate the role of prenatal prognostic markers obtained routinely by ultrasound examination and magnetic resonance imaging (MRI) in the prediction of development of postnatal pulmonary arterial hypertension (PAH) in isolated congenital diaphragmatic hernia (CDH). Methods: One hundred and ten cases of isolated CDH were referred to our fetal medicine unit between January 2004 and April 2013. Mortality and morbidity rates were reviewed for those presenting with postnatal PAH. The following prenatal markers were evaluated as potential predictive factors of PAH: liver position, side of the CDH defect, lung area to head circumference ratio (LHR) and observed/expected LHR (o/e‐LHR), which were measured by ultrasound, and observed/expected total fetal lung volume (o/e‐TFLV), which was measured by MRI. Univariable logistic regression was used to assess associations. Results: PAH was significantly associated with perinatal mortality and morbidity ( P < 0.001). The occurrence of PAH decreased significantly with an increasing LHR, o/e‐LHR and o/e‐TFLV and was significantly increased for cases with an intrathoracic liver, but not for those with right‐sided defects. Univariable regression revealed that o/e‐TFLV (odds ratio (OR), 0.9 (95% CI, 0.86–0.95); P < 0.05 for percentage unit change in o/e), LHR (OR, 0.19 (95% CI, 0.09–0.40); P < 0.05 for unit change), o/e‐LHR (OR, 0.95 (95% CI, 0.93–0.98); P < 0.05 for percentage unit change in o/e) and liver position (OR, 2.82 (95% CI, 1.13–7.00); P < 0.05 for intrathoracic liver) were significant predictors of subsequent PAH. No differences were found after adjusting for gestational age at delivery. The areas under the receiver–operating characteristics curve were 0.80 and 0.75 for o/e‐TFLV and o/e‐LHR, respectively. Conclusion: In cases of CDH, PAH is associated with high rates of mortality and morbidity. Routinely obtained prenatal markers, usually used for the assessment of pulmonary hypoplasia, are also relevant for the postnatal prediction of PAH. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.